2017
DOI: 10.1038/srep42301
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of maternal uteroplacental insufficiency on oxygen-induced retinopathy in offspring: removing bias of premature birth

Abstract: To address the hypothesis that maternal uteroplacental insufficiency (UPI) increases severity of retinopathy of prematurity, we developed a composite rat model of UPI and oxygen-fluctuations and removed premature birth as a confounding factor. Timed-pregnant Sprague-Dawley dams underwent bilateral uterine artery ligation or anesthesia (control) at e19.5. Full-term pups developed in room air (RA) or an oxygen-induced retinopathy (OIR) model. Isolectin-stained retinal flat-mounts were analyzed for percent of are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…This is supported by rodent studies from Becker et al [185], in which premature birth was uncoupled from uteroplacental insufficiency (UPI, a major component of preeclampsia) using a rat uterine artery ligation model. They found that in the setting of term gestation, uteroplacental insufficiency resulted in a significant decrease in avascular area and a trend towards reduced proliferative vascularization in the OIR model of ROP, supporting a relationship between placental insufficiency and ROP protection at the earliest stages of retinal vascular development [185]. If ROP protection in the setting of preeclampsia is actually the inverse effect-namely an empirically greater risk or ROP from non-preeclamptic spontaneous preterm births-it can still be argued that mechanisms underlying reduced likelihood of ROP development in the setting of preeclampsia will inform approaches toward normalizing retinal vascular development and ROP prevention.…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 67%
See 2 more Smart Citations
“…This is supported by rodent studies from Becker et al [185], in which premature birth was uncoupled from uteroplacental insufficiency (UPI, a major component of preeclampsia) using a rat uterine artery ligation model. They found that in the setting of term gestation, uteroplacental insufficiency resulted in a significant decrease in avascular area and a trend towards reduced proliferative vascularization in the OIR model of ROP, supporting a relationship between placental insufficiency and ROP protection at the earliest stages of retinal vascular development [185]. If ROP protection in the setting of preeclampsia is actually the inverse effect-namely an empirically greater risk or ROP from non-preeclamptic spontaneous preterm births-it can still be argued that mechanisms underlying reduced likelihood of ROP development in the setting of preeclampsia will inform approaches toward normalizing retinal vascular development and ROP prevention.…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 67%
“…preterm delivery [10,17]. This is supported by rodent studies from Becker et al [185], in which premature birth was uncoupled from uteroplacental insufficiency (UPI, a major component of preeclampsia) using a rat uterine artery ligation model. They found that in the setting of term gestation, uteroplacental insufficiency resulted in a significant decrease in avascular area and a trend towards reduced proliferative vascularization in the OIR model of ROP, supporting a relationship between placental insufficiency and ROP protection at the earliest stages of retinal vascular development [185].…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 77%
See 1 more Smart Citation
“…Intravitreal anti-VEGF in infants with only mild ROP or too high a dose of anti-VEGF may be harmful to the retina and to physiologic vascularity, potentially stimulating recurrent intravitreal neovascularization. These data provide insight into the observation that not all extremely premature infants, those born less than 1000 g birth weight or under 28 weeks gestational age, develop severe ROP, and it may be that some infants are able to induce protective mechanisms for survival and to avoid severe ROP 21,57…”
Section: Vegf Provides Protection For Neural and Glial Cellsmentioning
confidence: 93%
“…Therefore, we and other labs have experimentally recreated some of these stresses to understand their role in causing ROP features. Some of these include fluctuations in oxygenation,17,18 poor postnatal growth,19 poor infant oxidative reserve under conditions of increased oxidative signaling,20 and reduced ability to express protective factors to offset events from extreme prematurity 21…”
Section: Background: From Original Observations To Current Day Rop Inmentioning
confidence: 99%